An algorithm for generating permutation algebras using soft spaces. Issue 3 (4th May 2018) - Khalil, Shuker Mahmood; Khadhaer, Fatima Hameed
ABSTRACT: Soft set theory has recently gained significance for finding rational and logical solutions to various real-life problems, which involve uncertainty, impreciseness and vagueness. In this paper, we introduced an algorithm to find permutation algebras using soft topological space. Moreover, this class of permutation algebras is called even (odd) permutation algebras if its permutation is even (odd). Furthermore, new concepts in permutation algebras are investigated such as splittable permutation algebra and ambivalent permutation algebra. Furthermore, several examples are given to illustrate the concepts introduced in this paper.